NaX molecular sieve adsorbent with low silica-alumina ratio as well as preparation method and application of NaX molecular sieve adsorbent
The high-silicon-aluminum-specific NaX molecular sieve was synthesized by microwave method and the moisture-heat solid phase transformation technology was used to transform into NaX molecular sieve, which solved the problems of high cost and insufficient CO2 adsorption capacity when synthesizing low-silicon-aluminum-specific NaX molecular sieve in the prior art, and achieved the preparation of high-efficiency and low-cost spherical adsorbents with high CO2 adsorption capacity.
Patent Information
- Application Number
- CN202411921207.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has problems such as high cost, high environmental pressure and insufficient CO2 adsorption capacity when synthesizing low silicon-aluminum-based NaX molecular sieves.
The high-silicon-aluminum-specific NaX molecular sieve was continuously synthesized in sodium aluminate solution by microwave method, and the inorganic clay was transformed into NaX molecular sieve through humid and heat solid phase transformation technology, which simplified the process flow and improved the CO2 adsorption capacity.
The spherical low-silicon-aluminum-specific NaX molecular sieve adsorbent with high CO2 adsorption capacity is achieved efficiently and at low cost, solving the problems of high cost and environmental pressure in traditional methods, and at the same time improving the market competitiveness of the adsorbent.
Smart Images

Figure CN119838562A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic porous material molecular sieves, and particularly relates to a low silicon-aluminum ratio NaX molecular sieve adsorbent that can be used for efficient and deep removal of CO2 and a preparation method thereof. Background Art
[0002] In the field of cryogenic air separation, it is necessary to adsorb and remove trace amounts of CO2 in compressed gas. At present, the core component of the adsorbent used in the device is a low silicon-aluminum ratio NaX molecular sieve. For the synthesis of low silicon-aluminum ratio NaX molecular sieve, the industrialized method is the traditional hydrothermal crystallization method, including the sodium-potassium system hydrothermal crystallization method (GB 1580928, CN101289197A and CN101717094A) and the potassium-free system hydrothermal crystallization method (CN106315612A and CN 113880104B). Although the sodium-potassium system hydrothermal crystallization method can synthesize low silicon-aluminum ratio NaX molecular sieve more stably, the use of expensive potassium source and the subsequent complicated potassium ion exchange washing not only cause a substantial increase in the synthesis cost, but also produce a large amount of washing wastewater. Compared with the sodium-potassium system hydrothermal crystallization method, the potassium-free system hydrothermal crystallization method does not require the use of expensive potassium sources and subsequent complicated potassium ion exchange washing, but this method is very likely to produce type A molecular sieves, which is not conducive to obtaining NaX molecular sieves with high CO2 adsorption capacity.
[0003] Compared with the sodium-potassium system hydrothermal crystallization method and the potassium-free system hydrothermal crystallization method for synthesizing low silicon-aluminum ratio NaX molecular sieve, the aluminization method does not require the use of a potassium source, and the process is simpler. However, the crystallization method used in the existing aluminization method is still the traditional hydrothermal crystallization method. For example, patent CN202111333459.X discloses a method for preparing a low silicon-aluminum ratio NaX molecular sieve by low-temperature crystallization: using silicon source and aluminum source according to a certain ratio to prepare low silicon-aluminum ratio NaX molecular sieve seeds, adding a small amount of the seeds in the process of preparing low silicon-aluminum ratio NaX, a low silicon-aluminum ratio NaX raw powder with a silicon-aluminum ratio between 2.0 and 2.2 and high crystallinity can be prepared by one-step low-temperature crystallization. This technology does not require pre-aging, nor does it require the introduction of a potassium source. A low silicon-aluminum ratio NaX molecular sieve can be obtained directly through one-step low-temperature crystallization, but the aluminization time of this technology is relatively long, and the efficiency of aluminization is also relatively low, which is prone to insufficient desiliconization and aluminum supplementation. In addition, excessively high local temperature or alkalinity can easily lead to the formation of type A impurity crystals, and the concentration and alkalinity of the sodium aluminate solution used are relatively high, which places high demands on the equipment and solution preparation process.
[0004] Before the low silicon-aluminum ratio NaX molecular sieve is applied to industrial equipment, it needs to be granulated and formed. The existing preparation of spherical low silicon-aluminum ratio NaX molecular sieve adsorbent adopts a process of synthesizing the low silicon-aluminum ratio NaX molecular sieve raw powder and then granulating it to obtain a spherical low silicon-aluminum ratio NaX molecular sieve adsorbent. On the one hand, a large amount of alkaline wastewater will be generated in the raw powder synthesis process, and the economic and environmental pressure of treating these wastewaters is relatively large. On the other hand, the separation of the raw powder preparation and the molding phase not only lengthens the process flow but also increases the manufacturing cost. In order to further improve the adsorption performance of the spherical low silicon-aluminum ratio NaX molecular sieve adsorbent, it is usually necessary to convert the inorganic clay in the adsorbent into NaX molecular sieve by alkali liquid crystallization. There is a huge mass transfer resistance in the crystallization process of the granular molecular sieve adsorbent, and the inorganic clay in the adsorbent cannot be fully crystallized into NaX molecular sieve, resulting in the inorganic clay content in the final adsorbent is still high, and the abrasion of the adsorbent increases and the strength decreases, which has an adverse effect on industrial use. In addition, a large amount of waste alkali liquid will be generated during the crystallization process, further increasing the environmental pressure.
[0005] Patent application CN202311762509.5 discloses a high-efficiency molecular sieve adsorbent for deep purification of oxygenated substances and its preparation and application. The preparation process includes: 1) Molecular sieve synthesis: aluminum source, silicon source, alkali, template agent and water are mixed evenly to obtain a crystallization solution, and after aging, microwave hydrothermal crystallization is first performed and then traditional hydrothermal crystallization is performed to obtain EMT / 13X mixed crystal molecular sieve, followed by filter pressing to obtain a wet filter cake; 2) Granulation: The wet filter cake is dried, mixed evenly after adding inorganic additives and pore-forming agents, and dried after rolling granulation; 3) Calcination: Then it is placed in an oxygen-containing atmosphere and calcined to obtain an EMT / 13X composite molecular sieve adsorbent. The highly efficient removal of non-polar or polar oxygenated substances in low-carbon olefins is achieved, the adsorption capacity is increased by more than 30%, and the purification depth can reach less than 1ppb. However, the patent prepares an EMT / 13X composite molecular sieve adsorbent with EMT molecular sieve as the main active component. Since the adsorption capacity of EMT molecular sieve for CO2 is significantly weaker than that of 13X molecular sieve for CO2, it is not suitable for efficient removal of trace CO2 in cryogenic air separation. In addition, expensive template agents are used in its preparation process, and the high raw material input price also limits its application in the field of air separation from the cost perspective.
[0006] Therefore, in order to solve the above problems, the present invention proposes a new method and process for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent with high CO2 adsorption capacity. Summary of the invention
[0007] The purpose of the present invention is to provide a low silicon-aluminum ratio NaX molecular sieve adsorbent and its preparation method and application in order to overcome at least one defect of the above-mentioned prior art. The adsorbent has a high content of NaX molecular sieve and has a higher CO2 adsorption capacity.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] One of the technical solutions of the present invention is a low silicon-aluminum ratio NaX molecular sieve adsorbent, the silicon-aluminum ratio of the adsorbent is 1.95-2.10, the content of inorganic additives in the adsorbent is <3.0wt%, and the strength is ≥35.0N / particle; at 2.5mmHg and 25°C, its static CO2 adsorption capacity is ≥7.5wt%, and at 250mmHg and 25°C, its static CO2 adsorption capacity is ≥22.0wt%.
[0010] Furthermore, the silicon-aluminum ratio of the main active component, the low silicon-aluminum ratio NaX molecular sieve in the adsorbent, is 1.9-2.0; at 2.5 mmHg and 25°C, the static CO2 adsorption capacity of the main active component is ≥8.5wt%; at 250 mmHg and 25°C, the static CO2 adsorption capacity of the main active component is ≥24.5wt%.
[0011] The second technical solution of the present invention is to provide a method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent, wherein a high silicon-aluminum ratio NaX molecular sieve is used as a raw material to continuously synthesize a pure phase, high crystallinity low silicon-aluminum ratio NaX molecular sieve by microwave conversion in a sodium aluminate solution, and the manufacturing cost of the molecular sieve adsorbent is synergistically reduced by directly granulating the wet filter cake of the low silicon-aluminum ratio NaX molecular sieve after filter pressing, and further the inorganic auxiliary clay in the adsorbent is crystallized into NaX molecular sieve by a solid phase crystallization method under wet and hot conditions, so that the content of NaX molecular sieve in the adsorbent is maximized, and finally the prepared spherical low silicon-aluminum ratio NaX molecular sieve has a higher CO2 adsorption capacity and better market competitiveness on the basis of ensuring strength.
[0012] The specific method includes the following steps:
[0013] 1) Synthesis of low silicon-aluminum ratio NaX molecular sieve: uniformly dispersing high silicon-aluminum ratio NaX molecular sieve in sodium aluminate solution to form slurry, and obtaining low silicon-aluminum ratio NaX molecular sieve after microwave conversion of the slurry;
[0014] 2) Granulation: Inorganic additives are introduced into the slurry after microwave conversion, and the mixture is stirred evenly and filtered to obtain a wet cake. The wet cake is dried and a pore-forming agent is added and mixed evenly, and a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball is obtained after rolling granulation;
[0015] 3) Solid phase crystallization: the wet ball of the low silicon-aluminum ratio NaX molecular sieve adsorbent is sealed and heat treated, and after drying, a semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is obtained;
[0016] 4) Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an oxygen-containing atmosphere and calcined to obtain the low silicon-aluminum ratio NaX molecular sieve adsorbent, which is the target product.
[0017] Further, the silicon-aluminum ratio of the high silicon-aluminum ratio NaX molecular sieve in step 1) is 2.5-3.0:1; further, the silicon-aluminum ratio of the high silicon-aluminum ratio NaX molecular sieve is 2.7-3.0:1;
[0018] The sodium aluminate solution is prepared by dissolving an aluminum source in a high-concentration sodium hydroxide solution, wherein sodium is calculated as Na2O, aluminum is calculated as Al2O3, and the composition of the sodium aluminate solution is that the molar ratio of Na2O / Al2O3 is 0.1-5.0:1 and the molar ratio of H2O / Na2O is 100-200:1; the mass percentage of the sodium hydroxide solution is 30-60wt%.
[0019] The aluminum source is sodium metaaluminate or aluminum hydroxide. In particular, aluminum hydroxide is preferred as the aluminum source. When aluminum hydroxide is used as the aluminum source, it is preferably common aluminum hydroxide, and more preferably common aluminum hydroxide prepared by sintering process.
[0020] Furthermore, the content of high silicon-aluminum ratio NaX molecular sieve in the slurry of step 1) is 50-80wt%; the microwave power is 300-1000W, the microwave conversion temperature is 50-120°C, and the microwave conversion time is 0.5-4h.
[0021] Furthermore, the dry weight ratio of the inorganic additive to the NaX molecular sieve in step 2) is (10-30): (70-90);
[0022] The inorganic additive is one of halloysite or attapulgite and a combination thereof;
[0023] The thickness of the wet filter cake is ≤3 cm and the water content is 60-70 wt %; the drying conditions of the wet filter cake are: the drying temperature is 60-120 DEG C, the drying time is 0.5-12 h, and the water content of the dried filter cake is 45-55 wt %; the pore-forming agent is sesbania powder, maltodextrin or starch, and the amount of the pore-forming agent is 1-6 wt % of the total mass of the dried filter cake base.
[0024] Furthermore, the inorganic auxiliary agent is a mixture of halloysite and attapulgite at a mass ratio of 50-100:0-50. In particular, halloysite calcined at 400-700°C is preferred as the inorganic auxiliary agent.
[0025] Further, the heat treatment method described in step 3) is: placing a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in a closed container with a porous barrier at the bottom, and adding water to the bottom of the container; the heat treatment temperature is 80-150°C, and the heat treatment time is 2-48h; the drying temperature is 100-150°C, and the drying time is 0.5-12h;
[0026] The calcination conditions in step 4) are: carried out in a gas environment with an oxygen content of ≥50%, a calcination temperature of 400-600° C., and a calcination time of 1-8 hours.
[0027] The third technical solution of the present invention is to provide an application of a low silicon-aluminum ratio NaX molecular sieve adsorbent, and to apply the adsorbent to the efficient removal of CO2 impurities in cryogenic air separation.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention uses NaX molecular sieve with a relatively high silicon-aluminum ratio as raw material to continuously synthesize pure phase, high crystallinity low silicon-aluminum ratio NaX molecular sieve by microwave conversion in sodium aluminate solution, and then transforms inorganic clay into NaX molecular sieve by wet heat solid phase crystallization, and applies the prepared low silicon-aluminum ratio NaX molecular sieve adsorbent to the deep removal of CO2 in the field of deep cold air separation. The difficult problem of continuous, efficient and stable synthesis of low silicon-aluminum ratio NaX molecular sieve by microwave method is solved, and at the same time, the method of directly granulating and forming the low silicon-aluminum ratio NaX molecular sieve / inorganic clay mixed wet filter cake after filter pressing is proposed, which simplifies the process flow and reduces the manufacturing cost. In addition, the successful breakthrough of wet heat solid phase crystallization technology does not reduce the crushing strength of the adsorbent and can significantly increase the content of NaX molecular sieve in the adsorbent, and finally obtains a spherical low silicon-aluminum ratio NaX molecular sieve adsorbent with higher CO2 adsorption capacity.
[0030] (2) The present invention realizes for the first time the method of microwave aluminization for synthesizing pure phase, high crystallinity, low silicon-aluminum ratio NaX molecular sieve, which has higher synthesis efficiency, lower energy consumption and more sufficient migration at the molecular level than the traditional hydrothermal crystallization method. In addition, directly using a high silicon-aluminum ratio NaX molecular sieve as a raw material avoids the influence of the instability of the traditional crystallization liquid gelation process on the synthesis of low silicon-aluminum ratio NaX molecular sieve, while avoiding the use of expensive potassium sources and complex potassium ion exchange washing. The introduction of the microwave method can significantly improve the utilization rate of the sodium aluminate solution in the aluminization process, greatly reduce the preparation concentration and alkalinity of the sodium aluminate solution used, and at the same time solve the generation of type A impurities caused by local unevenness, greatly shorten the crystallization time, reduce the difficulty of synthetic operation, and realize the stable synthesis of low silicon-aluminum ratio NaX molecular sieve. In the present invention, only the caustic ratio and concentration, solid-liquid ratio and crystallization temperature of the sodium aluminate solution need to be simply regulated to achieve the synthesis of low silicon-aluminum ratio NaX molecular sieve, the process is simpler and more controllable, and the obtained low silicon-aluminum ratio NaX molecular sieve has more stable performance. Different from the conventional hydrothermal crystallization synthesis of low silicon-aluminum ratio NaX molecular sieve, the mother liquor in the present invention is simpler to recycle and utilize. The clarified mother liquor can be directly utilized multiple times only after sedimentation separation, without the need to supplement with fresh sodium aluminate solution.
[0031] (3) Different from traditional powder mixing, the present invention adds inorganic auxiliary clay to the crystallization liquid after microwave crystallization in advance, and the mixing in the form of slurry greatly improves the mixing uniformity of the low silicon-aluminum ratio NaX molecular sieve and the inorganic auxiliary clay, which is beneficial to improve the utilization rate of the active components in the spherical low silicon-aluminum ratio NaX molecular sieve adsorbent and reduce the discreteness of the adsorbent strength distribution. There is no need to introduce water, and the low silicon-aluminum ratio NaX molecular sieve / inorganic clay after pressure filtration is directly used as raw materials to obtain the finished molecular sieve adsorbent after granulation and molding, which not only avoids the use of a large amount of water washing of the original powder process, but also reduces one powder drying process, significantly shortens the process flow and reduces energy consumption, and also solves the problem of large amounts of wastewater generation and treatment.
[0032] (4) The present invention is the first to break through the technical bottleneck of NaX molecular sieve crystallization by solid-phase clay. Different from the existing powder crystallization and solid-liquid crystallization, the solid-phase crystallization technology proposed in the present invention does not require a large amount of alkali solution. It can achieve NaX molecular sieve crystallization under the action of steam by relying only on the alkalinity remaining in the adsorbent wet bulb. No crystallization wastewater is generated, and the crystallization process is green and environmentally friendly. After solid-phase crystallization, there is no need for solid-liquid separation process, which further shortens the process flow and reduces energy consumption. In addition, the residual alkali can ensure that the adsorbent still has sufficient crushing strength at extremely low inorganic clay content.
[0033] (5) Compared with the existing low silicon-aluminum ratio NaX molecular sieve adsorbent, the main active component of the adsorbent prepared by the present invention is the low silicon-aluminum ratio NaX molecular sieve, the secondary active component is the normal silicon NaX molecular sieve, and the inactive inorganic clay content is less than 3.0wt%. The CO2 adsorption capacity of the prepared low silicon-aluminum ratio NaX molecular sieve adsorbent is increased by ≧10%, meeting the demand for high-efficiency CO2 adsorbent in the field of deep cold air separation. In addition, under the same filling volume, the regeneration cycle and service life of the molecular sieve adsorbent can be significantly extended, and the regeneration switching frequency and operating cost are lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD spectrum of the low silicon-aluminum ratio NaX molecular sieve powder prepared in Example 1;
[0035] Figure 2 The static CO2 adsorption curve of the low silicon-aluminum ratio NaX molecular sieve powder prepared in Example 1;
[0036] Figure 3 The XRD spectrum of the low silicon-aluminum ratio NaX molecular sieve powder prepared in Example 2;
[0037] Figure 4 The static CO2 adsorption curve of the low silicon-aluminum ratio NaX molecular sieve powder prepared in Example 2;
[0038] Figure 5 It is a schematic diagram of the structure of a closed container with a porous partition at the bottom. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0040] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0041] For example, the closed container with a porous barrier at the bottom used in the heat treatment of the present invention has a structure such as Figure 5As shown, it includes a closed reactor 1 (which can be made of materials such as plastic and stainless steel that can withstand the heat treatment temperature), a porous partition 2 is provided at the bottom (generally, its pore size is smaller than the diameter of the low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball, and the material is the same as that of the closed reactor), and a water storage cavity 4 is provided between the porous partition 2 and the bottom of the closed reactor 1 for storing water. The low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball 3 to be treated is placed on the porous partition 2. During the heat treatment, the bottom of the closed reactor 1 is heated to make the water temperature in the water storage cavity 4 80-150° C., and the low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball 3 is heat treated.
[0042] Example 1
[0043] Synthesis of NaX molecular sieve with low silicon-aluminum ratio: First, sodium aluminate is used as an aluminum source, dissolved in a NaOH solution with a mass percentage of 50wt%, and a sodium aluminate solution with a composition of Na2O / Al2O3=1.0 and H2O / Na2O=100 is prepared. After removing impurities, a clarified sodium aluminate solution is obtained. NaX molecular sieve powder with a silicon-aluminum ratio of 2.7 is added to the obtained sodium aluminate solution, and a uniformly mixed slurry is obtained after continuous stirring, wherein the content of NaX molecular sieve powder accounts for 50% of the total mass of the slurry. Finally, the slurry is placed in a microwave reactor, the microwave power is set to 300W, and microwave conversion is performed at 120°C for 0.5h to obtain a crystallized solution of NaX molecular sieve with low silicon-aluminum ratio, and the NaX molecular sieve with low silicon-aluminum ratio can be prepared after filter pressing, washing, and drying.
[0044] The prepared powder was subjected to phase analysis, and the results are shown in Figure 1 ,from Figure 1 It can be seen that the powder is a pure phase, high crystallinity NaX molecular sieve. Further XRF testing shows that its framework SiO2 / Al2O3 ratio is 1.92.
[0045] The obtained low silicon-aluminum ratio NaX molecular sieve powder was subjected to a static CO2 adsorption test (the specific test method refers to the standard HG / T 2690-2012 13X molecular sieve), that is, the low silicon-aluminum ratio NaX molecular sieve powder was placed in a sealed container, and the container was filled with CO2 at a pressure of 1MPa, and allowed to stand for 1h. Figure 2 The static CO2 adsorption curve of the prepared low silicon-aluminum ratio NaX molecular sieve powder is shown in the figure. As can be seen from the figure, the static CO2 adsorption capacity of the prepared low silicon-aluminum ratio NaX molecular sieve powder is: 9.88wt% at 2.5mmHg (25°C) and 25.17wt% at 250mmHg (25°C).
[0046] Comparative Example 1
[0047] A static CO2 adsorption test was carried out using the 13X-L model low silicon-aluminum ratio NaX molecular sieve sold by Shanghai Suoyi as a typical external sample for comparison. The static CO2 adsorption capacity of the typical external sample was: 8.05wt% at 2.5mmHg (25°C), and 23.86wt% at 250mmHg (25°C).
[0048] It can be seen that the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve prepared in Example 1 is better than the static CO2 adsorption capacity of the typical sample in Comparative Example 1.
[0049] Example 2
[0050] Synthesis of NaX molecular sieve with low silicon-aluminum ratio: First, sodium aluminate is used as an aluminum source, dissolved in a 50wt% NaOH solution, and a sodium aluminate solution with a composition of Na2O / Al2O3=5.0 and H2O / Na2O=200 is prepared. After removing impurities, a clarified sodium aluminate solution is obtained. NaX molecular sieve powder with a silicon-aluminum ratio of 3.0 is added to the obtained sodium aluminate solution, and a uniformly mixed slurry is obtained after continuous stirring, wherein the content of NaX molecular sieve powder accounts for 50% of the total mass of the slurry. Finally, the slurry is placed in a microwave reactor, the microwave power is set to 300W, and microwave conversion is performed at 120°C for 0.5h. After filter pressing, washing, and drying, the NaX molecular sieve with low silicon-aluminum ratio can be prepared.
[0051] The prepared powder was subjected to phase analysis, and the results are shown in Figure 3 It can be seen that the powder is a pure phase, high crystallinity NaX molecular sieve. Further XRF testing shows that its framework SiO2 / Al2O3 ratio is 2.00.
[0052] The static CO2 adsorption performance of the obtained NaX molecular sieve was tested by the same test method as in Example 1. The results are as follows: Figure 4 The above is the static CO2 adsorption curve of the prepared low silicon-aluminum ratio NaX molecular sieve powder. As can be seen from the figure, the static CO2 adsorption capacity of the prepared low silicon-aluminum ratio NaX molecular sieve powder is: 9.73wt% at 2.5mmHg (25°C) and 24.97wt% at 250mmHg (25°C).
[0053] Example 3
[0054] Synthesis of NaX molecular sieve with low silicon-aluminum ratio: First, ordinary aluminum hydroxide is used as an aluminum source, dissolved in a NaOH solution with a mass percentage of 50wt%, and a sodium aluminate solution with a composition of Na2O / Al2O3=0.1 and H2O / Na2O=100 is prepared. After removing impurities, a clarified sodium aluminate solution is obtained. NaX molecular sieve powder with a silicon-aluminum ratio of 3.0 is added to the obtained sodium aluminate solution, and a uniformly mixed slurry is obtained after continuous stirring, wherein the content of NaX molecular sieve powder accounts for 50% of the total mass of the slurry. Finally, the slurry is placed in a microwave reactor, the microwave power is set to 300W, and microwave conversion is performed at 120°C for 0.5h. After filter pressing, washing, and drying, the NaX molecular sieve with low silicon-aluminum ratio can be prepared.
[0055] XRF testing shows that its skeleton SiO2 / Al2O3 ratio is 1.98.
[0056] Further testing of its static CO2 adsorption capacity showed that the static CO2 adsorption capacity of the prepared low silicon-aluminum ratio NaX molecular sieve powder was: 9.64wt% at 2.5mmHg (25°C) and 24.74wt% at 250mmHg (25°C).
[0057] Example 4
[0058] Synthesis of NaX molecular sieve with low silicon-aluminum ratio: First, ordinary aluminum hydroxide is used as an aluminum source, dissolved in a 50wt% NaOH solution, and a sodium aluminate solution with a composition of Na2O / Al2O3=5.0 and H2O / Na2O=100 is prepared. After removing impurities, a clarified sodium aluminate solution is obtained. NaX molecular sieve powder with a silicon-aluminum ratio of 2.8 is added to the obtained sodium aluminate solution, and a uniformly mixed slurry is obtained after continuous stirring, wherein the content of NaX molecular sieve powder accounts for 60% of the total mass of the slurry. Finally, the slurry is placed in a microwave reactor, the microwave power is set to 1000W, and microwave conversion is performed at 50°C for 4h. After filter pressing, washing, and drying, the NaX molecular sieve with low silicon-aluminum ratio can be prepared.
[0059] The prepared low silicon-aluminum ratio NaX molecular sieve powder was tested by XRF, and its framework SiO2 / Al2O3 ratio was 1.95.
[0060] The static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve powder was further tested, and its static CO2 adsorption capacity at 2.5 mmHg (25°C) was 9.59 wt%, and its static CO2 adsorption capacity at 250 mmHg (25°C) was 25.17 wt%.
[0061] Example 5
[0062] Synthesis of NaX molecular sieve with low silicon-aluminum ratio: First, ordinary aluminum hydroxide is used as an aluminum source, dissolved in a solution with a mass percentage of 50wt%, and a sodium aluminate solution with a composition of Na2O / Al2O3=5.0 and H2O / Na2O=100 is prepared. After removing impurities, a clarified sodium aluminate solution is obtained, and NaX molecular sieve powder with a silicon-aluminum ratio of 2.8 is added to the obtained sodium aluminate solution. After continuous stirring, a uniformly mixed slurry is obtained, in which the content of NaX molecular sieve powder accounts for 80% of the total mass of the slurry. Finally, the slurry is placed in a microwave reactor, the microwave power is set to 1000W, and microwave conversion is performed at 50°C for 4h. After filter pressing, washing, and drying, the NaX molecular sieve with low silicon-aluminum ratio can be prepared.
[0063] The prepared low silicon-aluminum ratio NaX molecular sieve powder was tested by XRF, and its framework SiO2 / Al2O3 ratio was 1.90.
[0064] The static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve powder was further tested, and its static CO2 adsorption capacity at 2.5 mmHg (25°C) was 9.41 wt%, and its static CO2 adsorption capacity at 250 mmHg (25°C) was 24.95 wt%.
[0065] Example 6
[0066] Granulation: First, according to the dosage ratio (dry basis) of 85wt% NaX molecular sieve and 15wt% halloysite (hebei hengguang halloysite is selected in this embodiment, 550℃ / 2h), a certain amount of halloysite is weighed and added to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and a uniformly dispersed slurry is obtained after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 120℃ for 0.5h to obtain a filter cake with a water content of 55wt%. Finally, 1wt% of sesbania powder is added to the filter cake, and after sufficient crushing, water is used as a binder, and rolling granulation is performed in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0067] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 80℃ for crystallization for 48h. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 150℃ for 4h to obtain the semi-finished product of low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0068] Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an atmosphere with an oxygen content of 50% and calcined at 400°C for 8 hours. After sieving, the finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent with a particle size of 1.6-2.4 mm is obtained.
[0069] Composition analysis of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that the content of inorganic additives in the adsorbent was 2.44wt%, the SiO2 / Al2O3 molar ratio was 1.95, and the strength was 36.8N / particle.
[0070] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 8.02 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.85 wt%.
[0071] Comparative Example 2
[0072] The low silicon-aluminum ratio NaX molecular sieve original powder of model 13X-L commercially available from Shanghai Suoyi Company was used to replace the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and the rest was the same as in Example 6.
[0073] The static CO2 adsorption capacity and strength tests of the obtained spherical NaX molecular sieve adsorbent showed that the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 6.24wt% (2.5mmHg, 25°C) and 20.24wt% (250mmHg, 25°C), and the strength was 32.5N / particle.
[0074] It can be seen that the spherical low-silicon-aluminum NaX molecular sieve adsorbent prepared by the present invention has a higher CO2 adsorption capacity.
[0075] Example 7
[0076] Granulation: First, according to the dosage ratio of 80wt% NaX molecular sieve and 20wt% halloysite (550℃ / 2h) (dry basis), a certain amount of halloysite is weighed and added to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and a uniformly dispersed slurry is obtained after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 120℃ for 1h to obtain a filter cake with a water content of 45wt%. Finally, 1wt% of sesbania powder is added to the filter cake, and after sufficient crushing, water is used as a binder, and rolling granulation is performed in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0077] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 80℃ for crystallization for 48h. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 150℃ for 4h to obtain the semi-finished product of low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0078] Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an atmosphere with an oxygen content of 50% and calcined at 400°C for 8 hours. After sieving, the finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent with a particle size of 1.6-2.4 mm is obtained.
[0079] Composition analysis of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that the content of inorganic additives in the adsorbent was 2.63wt%, the SiO2 / Al2O3 molar ratio was 2.02, and the strength was 38.2N / particle.
[0080] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 7.79 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.62 wt%.
[0081] Comparative Example 3
[0082] The low silicon-aluminum ratio NaX molecular sieve original powder of model 13X-L sold by Shanghai Suoyi was used to replace the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and the rest was the same as Example 7. Further testing of its static CO2 adsorption capacity showed that the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 6.57wt% (2.5mmHg, 25°C) and 20.23wt% (250mmHg, 25°C).
[0083] It can be seen that the spherical low-silicon-aluminum NaX molecular sieve adsorbent prepared by the present invention has a higher CO2 adsorption capacity.
[0084] The adsorbents obtained in the above Example 7 and Comparative Example 3 were used to carry out an adsorption and removal experiment on trace amounts of CO2 in compressed gas: dry air with a pressure of 0.3-0.4 MPa and a CO2 content of 350 ppm was used as a raw material and passed into a bed containing 200 g of the adsorbent.
[0085] The removal experiment at room temperature shows that compared with the adsorbent of Comparative Example 3, the switching period of the adsorbent sample of Example 7 is extended by about 15%.
[0086] Example 8
[0087] Granulation: First, according to the dosage ratio of 80wt% NaX molecular sieve and 20wt% halloysite (550℃ / 2h) (dry basis), a certain amount of halloysite is weighed and added to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and a uniformly dispersed slurry is obtained after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 120℃ for 1h to obtain a filter cake with a water content of 45wt%. Finally, 1wt% of sesbania powder is added to the filter cake, and after sufficient crushing, water is used as a binder, and rolling granulation is performed in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0088] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 150℃ for crystallization for 2 hours. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 150℃ for 4 hours to obtain a semi-finished low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0089] Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an atmosphere with an oxygen content of 50% and calcined at 400°C for 8 hours. After sieving, the finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent with a particle size of 1.6-2.4 mm is obtained.
[0090] Composition analysis of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that the content of inorganic additives in the adsorbent was 2.74wt%, the SiO2 / Al2O3 molar ratio was 2.04, and the strength was 35.9N / particle.
[0091] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 7.91 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 23.02 wt%.
[0092] Example 9
[0093] Granulation: First, weigh a certain amount of halloysite and attapulgite according to the dosage ratio (dry basis) of 80wt% NaX molecular sieve, 10wt% halloysite (550℃ / 2h) and 10wt% attapulgite, and add them to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and obtain a uniformly dispersed slurry after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 120℃ for 1h to obtain a filter cake with a water content of 45wt%. Finally, add 1wt% sesbania powder to the filter cake, and after sufficient crushing, use water as a binder, roll granulate in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0094] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 150℃ for crystallization for 2 hours. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 150℃ for 4 hours to obtain a semi-finished low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0095] Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an atmosphere with an oxygen content of 50% and calcined at 600°C for 1 hour. After sieving, the finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent with a particle size of 1.6-2.4 mm is obtained.
[0096] Composition analysis of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that the content of inorganic additives in the adsorbent was 2.39wt%, the SiO2 / Al2O3 molar ratio was 1.97, and the strength was 36.3N / particle.
[0097] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 7.97 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.72 wt%.
[0098] Comparative Example 3
[0099] The low silicon-aluminum ratio NaX molecular sieve original powder of model 13X-L sold by Shanghai Suoyi was used to replace the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and the rest was the same as Example 9. Further testing of its static CO2 adsorption capacity showed that the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 6.45wt% (2.5mmHg, 25°C) and 19.6wt% (250mmHg, 25°C).
[0100] It can be seen that the spherical low-silicon-aluminum NaX molecular sieve adsorbent prepared by the present invention has a higher CO2 adsorption capacity.
[0101] Example 10
[0102] Granulation: First, weigh a certain amount of halloysite according to the dosage ratio (dry basis) of 80wt% NaX molecular sieve and 20wt% halloysite (700℃ / 2h) and add it to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and obtain a uniformly dispersed slurry after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 120℃ for 1h to obtain a filter cake with a water content of 45wt%. Finally, add 1wt% sesbania powder to the filter cake, and after sufficient crushing, use water as a binder and roll granulate in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0103] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 150℃ for crystallization for 2 hours. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 150℃ for 4 hours to obtain a semi-finished low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0104] Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an atmosphere with an oxygen content of 50% and calcined at 400°C for 8 hours. After sieving, the finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent with a particle size of 1.6-2.4 mm is obtained.
[0105] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 7.90 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.72 wt%.
[0106] Embodiment 11
[0107] Granulation: First, according to the dosage ratio of 80wt% NaX molecular sieve and 20wt% halloysite (700℃ / 2h) (dry basis), a certain amount of halloysite is weighed and added to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and a uniformly dispersed slurry is obtained after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 60℃ for 12h to obtain a filter cake with a water content of 50wt%. Finally, 6wt% of sesbania powder is added to the filter cake, and after sufficient crushing, water is used as a binder, and rolling granulation is performed in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0108] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 120℃ for crystallization for 4 hours. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 100℃ for 6 hours to obtain a semi-finished low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0109] Calcination: The low silicon-aluminum ratio NaX molecular sieve adsorbent semi-finished product is placed in an atmosphere with an oxygen content of 60% and calcined at 400°C for 8 hours. After sieving, a low silicon-aluminum ratio NaX molecular sieve adsorbent finished product with a particle size of 1.6-2.4 mm is obtained.
[0110] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 8.02 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.46 wt%.
[0111] Example 12
[0112] Granulation: First, according to the dosage ratio of 90wt% NaX molecular sieve and 10wt% halloysite (700℃ / 2h) (dry basis), a certain amount of halloysite is weighed and added to the low silicon-aluminum ratio NaX molecular sieve crystallization liquid after microwave conversion in Example 1, and a uniformly dispersed slurry is obtained after sufficient stirring. Then, the slurry is filtered by plate filter press equipment to obtain a filter cake with a thickness of 2cm and a water content of 60wt%. The filter cake is dried at a temperature of 60℃ for 12h to obtain a filter cake with a water content of 50wt%. Finally, 6wt% of sesbania powder is added to the filter cake, and after sufficient crushing, water is used as a binder, and rolling granulation is performed in a sugar coating machine to obtain a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball.
[0113] Solid phase crystallization: Place the wet ball of low silicon-aluminum ratio NaX molecular sieve adsorbent in a plastic barrel with a porous partition at the bottom, add enough water to the bottom of the plastic barrel, seal it and place it at 120℃ for crystallization for 4 hours. Then place the crystallized low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in an oven at 100℃ for 6 hours to obtain a semi-finished low silicon-aluminum ratio NaX molecular sieve adsorbent.
[0114] Calcination: The low silicon-aluminum ratio NaX molecular sieve adsorbent semi-finished product is placed in an atmosphere with an oxygen content of 60% and calcined at 400°C for 8 hours. After sieving, a low silicon-aluminum ratio NaX molecular sieve adsorbent finished product with a particle size of 1.6-2.4 mm is obtained.
[0115] The static CO2 adsorption capacity test of the prepared spherical low silicon-aluminum ratio NaX molecular sieve adsorbent showed that at 2.5 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 7.85 wt%; at 250 mmHg (25°C), the static CO2 adsorption capacity of the low silicon-aluminum ratio NaX molecular sieve adsorbent was 22.78 wt%.
[0116] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A low silicon-aluminum ratio NaX molecular sieve adsorbent, characterized in that: The silicon-aluminum ratio of the adsorbent is 1.95-2.10, the content of inorganic additives in the adsorbent is less than 3.0wt%, and the strength is ≥35.0N / particle; at 2.5mmHg and 25°C, its static CO2 adsorption capacity is ≥7.5wt%, and at 250mmHg and 25°C, its static CO2 adsorption capacity is ≥22.0wt%.
2. The low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 1, characterized in that: The main active component of the adsorbent, the low silicon-to-aluminum ratio NaX molecular sieve, has a silicon-to-aluminum ratio of 1.9 to 2.0; at 2.5 mmHg and 25° C., the static CO2 adsorption capacity of the main active component is ≥8.5 wt %; at 250 mmHg and 25° C., the static CO2 adsorption capacity of the main active component is ≥24.5 wt %.
3. A method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: 1) Synthesis of low silicon-aluminum ratio NaX molecular sieve: uniformly dispersing high silicon-aluminum ratio NaX molecular sieve in sodium aluminate solution to form slurry, and obtaining low silicon-aluminum ratio NaX molecular sieve powder after microwave conversion of the slurry; 2) Granulation: Inorganic additives are introduced into the slurry after microwave conversion, and the mixture is stirred evenly and filtered to obtain a wet cake. The wet cake is dried and a pore-forming agent is added and mixed evenly, and a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball is obtained after rolling granulation; 3) Solid phase crystallization: the wet ball of the low silicon-aluminum ratio NaX molecular sieve adsorbent is sealed and heat treated, and after drying, a semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is obtained; 4) Calcination: The semi-finished product of the low silicon-aluminum ratio NaX molecular sieve adsorbent is placed in an oxygen-containing atmosphere and calcined to obtain the low silicon-aluminum ratio NaX molecular sieve adsorbent, which is the target product.
4. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 3, characterized in that: The silicon-aluminum ratio of the high silicon-aluminum ratio NaX molecular sieve described in step 1) is 2.5-3.0:1; The sodium aluminate solution is prepared by dissolving an aluminum source in a high-concentration sodium hydroxide solution, wherein sodium is calculated as Na2O, aluminum is calculated as Al2O3, and the composition of the sodium aluminate solution is that the molar ratio of Na2O / Al2O3 is 0.1-5.0:1 and the molar ratio of H2O / Na2O is 100-200:1; the mass percentage of the sodium hydroxide solution is 30-60wt%.
5. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 4, characterized in that: The silicon-aluminum ratio of the high silicon-aluminum ratio NaX molecular sieve is 2.7-3.0:1; The aluminum source is sodium metaaluminate or aluminum hydroxide.
6. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 3, characterized in that: The content of high silicon-aluminum ratio NaX molecular sieve in the slurry of step 1) is 50-80wt%; the microwave power is 300-1000W, the microwave conversion temperature is 50-120°C, and the microwave conversion time is 0.5-4h.
7. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 3, characterized in that: The dry weight ratio of the inorganic additive to the NaX molecular sieve in step 2) is (10-30): (70-90); The inorganic auxiliary agent is one or a combination of halloysite or attapulgite. The thickness of the wet filter cake is ≤3 cm and the water content is 60-70 wt %; the drying conditions of the wet filter cake are: the drying temperature is 60-120 DEG C, the drying time is 0.5-12 h, and the water content of the dried filter cake is 45-55 wt %; the pore-forming agent is sesbania powder, maltodextrin or starch, and the amount of the pore-forming agent is 1-6 wt % of the total mass of the filter cake base.
8. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 7, characterized in that: The inorganic auxiliary agent is prepared by mixing halloysite and attapulgite in a mass ratio of 50-100:0-50.
9. The method for preparing a low silicon-aluminum ratio NaX molecular sieve adsorbent according to claim 3, characterized in that: The heat treatment method described in step 3) is: placing a low silicon-aluminum ratio NaX molecular sieve adsorbent wet ball in a closed container with a porous barrier at the bottom, and adding water to the bottom of the container; the heat treatment temperature is 80-150° C., and the heat treatment time is 2-48 hours; the drying temperature is 100-150° C., and the drying time is 0.5-12 hours; The calcination conditions in step 4) are: carried out in a gas environment with an oxygen content of ≥50%, a calcination temperature of 400-600° C., and a calcination time of 1-8 hours.
10. An application of a low silicon-aluminum ratio NaX molecular sieve adsorbent as claimed in claim 1 or 2, characterized in that: The adsorbent is applied to the efficient removal of CO2 impurities in cryogenic air separation.
Citation Information
Patent Citations
Method for preparing low-silicon X-shaped molecular screen LSX
CN101289197A
Sodium-type low-silicon X-type molecular sieve raw powder and preparation method thereof
CN101717094A
Preparation method of X type molecular sieve with low silica-alumina ratio
CN106315612A
Method for preparing NaX molecular sieve with low silica-alumina ratio through low-temperature crystallization
CN113880104A
A method for preparing low silicon-aluminum ratio NaX molecular sieve by low temperature crystallization
CN113880104B